Tracking the Land Use Land Cover Changes from 2000 to 2018 in Local Area of East Java Province - Indarto, Indarto; Hakim, Farid Lukman (Bulletin of Geography. Socio-economic Series, 2021)
Land Use Land Cover (LULC) change represent the human influences on the natural ecosystem. This study aims to analyze LULC change in the eastern part of East Java. The region covers an area ± 3320,3 km2. The change analysed by comparing two editions of maps (the National Digital Map and Landsat-8). The five subsets explore to understand the change. The development of transportation infrastructure, industrial sites, agricultural sectors, tourism, urbanisation and sub-urbanisation caused the significant LULC change. Regional development has increased the built-up area by 8,66% (287.4 km2) of the total area. Then increase of the paddy-field by 13.93% and forest-plantation area by 7.20%. Oppositely, the development decreases rural areas by -29.43% (977.2 km2) and water body by -0.88 % (29.1 km2). The LULC change has significantly converted the natural to human-induced landscapes that potentially fragile to disasters in this region.